The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1194/jlr.m200319-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of intestinal cholesterol absorption in humans is not related to apoE phenotype

Abstract: The present study investigated the role of apolipoprotein E (apoE) phenotype on intestinal cholesterol absorption and cholesterol synthesis. Studies were carried out in eight subjects homozygous for the apoE4 and 12 subjects homozygous for the E2 allele (six normocholesterolemic volunteers and six patients with type III hyperlipoproteinemia). Cholesterol absorption did not differ between the three groups of subjects and averaged 38 ؎ 2% (mean ؎ SEM) in normolipemic E2/2, 37 ؎ 4% in type III hyperlipemic E2/2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
2
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 27 publications
0
20
2
1
Order By: Relevance
“…In addition, none of the previous studies controlled for known variations in cholesterol absorption associated with apo E or apo A-IV genotypes and all had less stringent dietary control than in this investigation. 16,44,45 Although a recent study showed no difference between different apo E alleles on cholesterol absorption and metabolism, 46 this observation awaits further confirmation because previous studies demonstrated apo E genotype-related differences in cholesterol absorption. 44,45,47,48 In summary, in a healthy population with apo A-IV 1/1 and apo E 3/3 genotypes, supplementation with CDCA or DCA enriched bile with the corresponding bile acid.…”
Section: Discussionmentioning
confidence: 66%
“…In addition, none of the previous studies controlled for known variations in cholesterol absorption associated with apo E or apo A-IV genotypes and all had less stringent dietary control than in this investigation. 16,44,45 Although a recent study showed no difference between different apo E alleles on cholesterol absorption and metabolism, 46 this observation awaits further confirmation because previous studies demonstrated apo E genotype-related differences in cholesterol absorption. 44,45,47,48 In summary, in a healthy population with apo A-IV 1/1 and apo E 3/3 genotypes, supplementation with CDCA or DCA enriched bile with the corresponding bile acid.…”
Section: Discussionmentioning
confidence: 66%
“…However, the use of plant sterols cannot be defi nitely recommended before prospective clinical trials with hard cardiovascular end points have shown their effectiveness to reduce cardiovascular risk ( 51 ). Previous studies addressing the effects of the APOE genotype on the noncholesterol sterol to cholesterol ratios have been confl icting ( 52,53 ). In our cohort, the combined APOE 3/4 and 4/4 genotypes were associated with a high lathosterol to cholesterol ratio, whereas the cholestanol, campesterol, and sitosterol to cholesterol ratios were not related to the APOE genotype.…”
Section: Discussionmentioning
confidence: 99%
“…Data on the relationships of the APOE genotype with cholesterol absorption and synthesis are controversial (35,36). Additional adjustment for APOE variants did not affect the associations of cholesterol homeostasis with the severity of CAD.…”
Section: Discussionmentioning
confidence: 99%